Accessible art for the blind and visually impaired in London museums - Wendorff, Anna (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
This is the first time that a Polish academic has discussed the experience of teaching the disabled in British museums. The book exemplifies the researcher’s professionalism and expertise in the discussed area on a global scale. From a review by Professor Waldemar Deluga, PhD In her publication, the author interestingly juxtaposes topics that are usually dealt with separately, namely audio description, anthropology of the senses and accessibility in museums. lt is especially engaging to follow the analysis of these three components and their intersection in one book. The case study of London museums is also noteworthy, as it may be of particular interest to Polish readers: art historians, museologists and those concerned with accessibility in museum institutions. The monograph has an interdisciplinary character, drawing on research in art history, translation studies and anthropology, which I consider to be its greatest strength. I also highly appreciate the presented case study of London museums, which can become an example of good practice for Polish artists, curators and museum professionals. From a review by Associate Professor Łukasz Chmielewski, PhD